Kajian Teori Peserta Didik Usia 13-17 Tahun Dan Dampak Negatif Multimedia - Umbu Ndapa Kahali; Jonidius Illu (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The electronic media discussed in this paper are temporarily only focused on the use of internet media and professions which are currently trending. This is because it is the use of the internet that is currently the most popularly used by many people, apart from being something that can be categorized as something that is 'booming'. It should be underlined, with the existence of technological developments in the future, it is possible to use other network media besides the internet in e-commerce. So our thinking should not only be fixated on the mere use of internet media. Community service this time is to provide training/debriefing for students aged 13-17 years. The negative impact arising from the effectiveness of TikTok's social media has also made it impossible for them to play TikTok. Teenagers often lose track of time and neglect other work or become obsessed with the TikTok application itself. There is still a lot of content on the TikTok application that is not appropriate for teenagers to see. The positive impacts of using social media are as follows: a. Can make social media a means or media used to communicate with other users. Through this communication individuals can have a motivation to develop themselves to be better. For example, having a desire to study hard is obtained from the results of interpersonal communication with other users. b. Develop yourself by honing capacity through videos watched on social media. For example, by watching a video that has a moral message for the lives of teenagers, they should not give up in carrying out the educational process they are facing and continue to be enthusiastic and persistent in achieving all their desires. c. Can express emotions owned by teenagers through a post on social media. Apart from that, the existence of positive content on social media makes individuals have positive reinforcement to form better character or self-development. Meanwhile, the negative impact obtained from the use of social media which is used as a medium for strengthening character for adolescents can be seen through accessing the negative content chosen by teenagers. In this research, the writer or researcher uses qualitative researchers in order to get the right sources to develop hypotheses related to the subject or research topic. A proper qualitative approach involves analyzing and describing every source, information, and data in the literature. Qualitative research emphasizes the depth of data obtained by researchers. The deeper and more detailed the data obtained, the better the quality of this qualitative research. So, qualitative research is a research approach used by the author to describe information and data analysis that is relevant to the topic of discussion.